EVALUATE THE PROCESS OF STEREOTAXIC INJECTION OF THE HIPPOCAMPUS BY A HOME - MADE SYRINGE - Nguyen Ha Hoa; Do Xuan Hai; Do Duc Thuan; Nguyen Huyen Trang; Nguyen Thi Thanh Binh; Khuat Thi Hue (Tạp chí Y học Quân sự, 2023)
Purpose: We aimed to to evaluate the process of stereotaxic injection of the rat hippocampus; determined the volume of solution, and the speed of the injection of the solution into the hippocampus of the rat by a home-made syringe. Methods: Experimental study, controlled description. Results: The study identified the process of stereotaxic injection of the rat’s hippocampus (including eight steps: immobilizing the rat to the positioning frame; exposing the skull bones to find Bredma, Lamda points; positioning the hippocampus on the skull; drilling the skull; putting the needle into the hippocampus; injecting the solution; saving the needle; pulling out the needle). The average time of anesthesia for both groups was 31.8 ± 7 minutes. The average time to perform the process of injection with a solution was 38 ± 4.07 minutes. Determine the coordinates of stereotaxic injection of the rat hippocampus (coordinates: AP = 4 mm; ML = 2.2 mm; DV = 3 mm); injection dose of 2.5 μl of solution; injection speed 1.13 μl/min. The dose and speed of the injection of the solution as above did not affect the health of the rat.